A General Strategy for the Construction of NIR‐emitting Si‐rhodamines and Their Application for Mitochondrial Temperature Visualization. Issue 17 (28th July 2020) - Tang, Weiguo; Gao, Han; Li, Jiaxin; Wang, Xianhui; Zhou, Zhikuan; Gai, Lizhi; Feng, Xin Jiang; Tian, Jiangwei; Lu, Hua; Guo, Zijian
Abstract: Si‐rhodamine (SiR) is an ideal fluorophore because it possesses bright emission in the NIR region and can be implemented flexibly in living cells. Currently, several promising approaches for synthesizing SiR are being developed. However, challenges remain in the construction of SiR containing functional groups for bioimaging application. Herein, we introduce a general and simple approach by a condensation reaction of diarylsilylether and arylaldehyde in o ‐dichlorobenzene to synthesize a series of SiRs bearing various functional substituents. These SiRs have moderate to high quantum efficiency, tolerance to photobleaching, and high water solubility as well as NIR emitting, and their NIR fluorescence properties can be controlled through the photoinduced electron transfer (PET) mechanism. Fluorescence OFF‐ON switching effect is observed for SiR 9 in the presence of acid, which is rationalized by DFT/TDDFT calculations. Moreover, reversible stimuli response toward temperature is achieved. Since positive charge enables mitochondrial targeting ability and chloromethyl unit can covalently immobilize the dyes onto the mitochondrial via click reaction between the benzyl choride and protein sulfhydryls, SiR 8 is identified as a valuable fluorescent marker to visualize the morphology and monitor the temperature change of mitochondria with high photostability. Abstract : A general and simple approach to synthesize Si‐rhodamines bearing various functional substituents is reported. In addition, their use for monitoring the temperature change of mitochondria is demonstrated.